Production of Industrial-Grade Monoclinic Lead Chromate (PbCrO4) from Indigenous Chromite ore for Paint Pigment Utilization - Ayinla, Kuranga. I.; Baba, Alafara A.; Tripathy, Bankim C.; Dwari, Ranjan K. (Journal of Nepal Chemical Society, 2024)
Decades of use have proven that lead chromate (PbCrO4) powder is an excellent paint pigment material. Unfortunately, practically this entire superb chromate compound used for decorative systems, protective systems, and mass dyeing of paper and polymer materials is conventionally made using inorganic synthetic chromium salts. In this study, we reported a promising simple, low-cost lead chromate production route derived from chromite ore from Nigeria. The Nigerian chromite ore was roasted in a 1:1 NaOH salt and then leached with water at 60°C. Lead nitrate was added to the leached liquor to further co-precipitate it. The resulting precipitate was then cleaned in ethanol and oven dried for ten hours at 80°C. The experimental results showed that lead ion concentration, temperature and flow rate have large influence on lead chromate precipitation, and the precipitation data fit a diffusion model. The activation energy of lead precipitation obtained was 4.76 kJ/mol, and the reaction order was 0.873 nearly one in relation to the concentration of lead ion. Additionally, XRD, FT-IR, and SEM/EDS comparative investigation of the properties established which favourable paint pigment performance similar to that of commercial industrial lead chromate powder in a range of all established physicochemical properties clarified the developing direction of research on lead chromate synthesis from Chromite leached liquor.